Agmatine protects against MAFLD via decreasing RBM15/IGF2BP2-mediated m6A modification of SREBP1 - Guangkui Bu; Yu Li; Guangfu Lin; Lichun Han; Deyi Chen; Xiaoping Lv (Molecular Biology Reports, 2026)

Individual and combined exposures to polystyrene nanoplastics and benzophenone-3 induce developmental, behavioral and transcriptomic impairments in marine larval clownfish (Amphiprion frenatus) - Yankun Zhang; Fang Lin; Shaobai Wen; Muhammad Junaid; Han Qian; Xiaoping Diao (Marine Pollution Bulletin, 2026)

Superhydrophobic enhanced nanofluidic channels: Preparing a self-healing, anti-icing coating - Yonghao Zhu; Xia Zhao; Xiaoping Guo; Donald Terry Greenfield; Jizhou Duan; Shan Lin; Baorong Hou (Chemical Engineering Journal, 2026)

Predictive gas recirculation control for CO2-modified atmosphere treatment in a full-scale concrete maize silo using conditional multi-step forecasting - Jie Lin; Kun Hu; Xiaoping Yan; Haoyu Wen; Xiaoyu Zhang; Yining Wu; Yuanyi Luo; Hongwei Xiao (Journal of Stored Products Research, 2026)

Intelligent aeration technologies in grain storage: A comprehensive review of multi-physics modeling and AI-driven control - Xiaoyu Zhang; Jiale Guo; Yanhong Liu; Yuanyi Luo; Shuanglin Wang; Deqing Wang; Jie Lin; Kun Hu; Haoyu Wen; Yining Wu; Xiaoping Yan (Journal of Stored Products Research, 2026)

Land-use-driven terrestrial inputs and fresh-seawater mixing jointly shape sediment organic nitrogen in the Pearl River Estuary - Jia Yang; Pengju Li; Yunchao Wu; Jinlong Li; Feng Ye; Yuanbi Yi; Shicheng Lin; Ling Zhang; Zhijian Jiang; Songlin Liu; Xiaoping Huang; Ding He (Science China Earth Sciences, 2026)

Hierarchically porous UiO-66-(OH)2@COF-OMe composites with multiple binding sites for synergistic extraction of polybrominated diphenyl ethers from surface waters - Jingpu Tang; Wentao Lan; Hongyan Zeng; Chenchen Lin; Xiaoping Wu (Journal of Hazardous Materials, 2026)

Environmental Factors Drive Neurodegenerative Diseases Through Glutamate Excitotoxicity: A Convergent Mechanistic Pathway - Yulu He; Tingting Yi; Meixin Min; Ke Xu; Huan Lin; Rong Xu; Dan Deng; Xiaoping Xiao (Neuroscience Bulletin, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

Microbial necromass carbon accumulation in degraded Moso bamboo forests is driven by bacterial r-strategy shift and enhanced carbon use efficiency - Lin Xu; Xiaoping Tang (European Journal of Soil Biology, 2026)

Sustainable multifunctional packaging films based on chitosan and food waste-derived carbon nanodots for fruit preservation - Ying Ren; Dan Chen; Shiyu Lin; Xiaoping Fan; Liming Cao (Journal of Food Engineering, 2026)

Strain-specific effects of lactic acid bacteria on rambutan juice fermentation: Insights from physicochemical, volatile, and non-volatile profiles - Jie Zhu; Jianxun Li; Xiaoping Hu; Kun Cai; Weimin Zhang; Xue Lin (Food Chemistry, 2026)

Effect of ivarmacitinib on swelling and tenderness in small and large joints and imaging changes in patients with moderate-to-severe RA: a post hoc analysis of a phase III clinical trial - Yuxiang Han; Meng Ding; Shaoxin Cui; Yu Tian; Yushu Yang; Xuying Liu; Lin Yang; Xiaoping Wang; Hongtao Jin; Huifang Guo; Haixue Dai; Shanshan Yin; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Ablation of FBXO38 triggers lysosome-dependent STING degradation to drive chemotherapy resistance in cervical cancer - Xihua Shen; Qi Liu; Yan Li; Xiaoping Ma; Cengceng Lu; Rongyan Ma; Rui Han; Zhiyi Lin; Hu Han (Apoptosis, 2026)

17β-Estradiol alleviates cognitive deficits by modulating fear memory reconsolidation in a PTSD rat model - Han Wang; Han Lin; Zilong Zhong; Baoying Jiang; Siyi Li; Jiahao Tang; Xiaoping Zhou; Guohui Zhu; Yang Liu; Wenhao Han; Jinhua Dou; Lin Sun (Psychopharmacology, 2026)

Aging enhances the ecological toxicity of polyethylene microplastics to marine medaka larvae (Oryzias melastigma) - Shaobai Wen; Jin Liu; Bigui Lin; Na Li; Xiaoping Diao (Journal of Environmental Management, 2026)

Improving fermentation efficiency and aroma quality of Shanlan Rice wine: Co-fermentation with selected dominant microorganisms from Shanlan Qubing - Longsheng Chen; Jianxun Li; Yaofei Hao; Jiamu Kang; Xiaoping Hu; Lu Wang; Xue Lin (Food Research International, 2026)

Integrated plastic film and straw mulching enhances potato tuber yield in mountainous regions by optimizing rhizospheric metabolites and root–microbe interactions - Kang Du; Xinyue Yang; Zhenpeng Deng; Xi Lin; Mengyuan Hu; Rui Jiang; Guolian Zheng; Xiaoping Yi; Xun Liu; Changwen Lyu; Jichun Wang (Field Crops Research, 2026)

Review: Synergistic effects of environmental pollutants: Multiple stressors driving the transmission of vector-borne diseases and the vicious cycle - Tingting Liu; Jia Wang; Minghao Yu; Yining Li; Huan Lin; Dan Deng; Xiaolu Shi; Xiaoping Xiao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Rhomboid Domain Containing 2 (RHBDD2) is Upregulated and Responds to Cisplatin-Induced DNA Damage in Esophageal Cancer - Youxiang Ding; Lin Zhou; Xintao He; Lin Li; Xiaoping Wang (Biochemical Genetics, 2026)

Assessing CO2-Modified atmosphere fumigation in a concrete maize silo for feasibility, gas distribution, and insect control efficacy - Jie Lin; Yuanyi Luo; Shuanglin Wang; Xiaoping Yan; Kun Hu; Hongwei Xiao (Journal of Stored Products Research, 2026)

Single-atom Cu nanozyme anchored on carbon nitride with enhanced peroxidase-like activity for colorimetric detection of foodborne pathogens - Fengyu Guo; Hua Lei; Qian Yang; Nana Jin; Xinyang Zhang; Jianhan Lin; Ruibing Hu; Baocheng Zhou; Wen Wang; Hua Yang; Xiaoping Dong (Journal of Hazardous Materials, 2026)

MnO-modified corn stalk biochar for catalytic ozonation of tetracycline hydrochloride: Mechanism, pathways and environmental risk assessments - Huajun Xu; Yunhao Yu; Tao Ye; Lin Miao; Baocheng Zhou; Pengfei Sun; Xiaoping Dong (Journal of Environmental Chemical Engineering, 2026)

Unraveling the critical role of nanoplastics in governing the interfacial behavior and toxicity evolution of ciprofloxacin during Fenton oxidation process - Hanjun Zhu; Haishuai Cui; Guopei Huang; Hai Yang; Jukun Xiong; Meimei Ran; Xiaoping Lin; Quan Wan; Lele Yang; Zelin Xu; Xin Nie (Chemical Engineering Journal, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

The growth-promoting effect and mechanism of microalgae on plants in PAHs contaminated soil - Yuechang Wang; Shengnan Wang; Lin-Lan Zhuang; Shuang Liu; Yuanjun Su; Zhen Hu; Xiaoping Wang; Shaoming Cui; Gang Peng (Journal of Environmental Sciences, 2025)

Optimization of coagulation process and its influence on membrane fouling for Anaerobic-Anoxic-Oxic-Anoxic Membrane Bioreactor (A2OA-MBR) - Xiaoping Tan; Ke Kuang; Jie Li; Caijing Lai; Zebin Chen; Ziyuan Wang; Wei Song; Yi Wu; Dachao Lin; Xing Du (Journal of Environmental Sciences, 2025)

Atmospheric nitrogen deposition to cropland in Fujian province, China - Ziyin Yu; Mengjuan Han; Zhang Wen; Wenqing Li; Changzheng Wu; Xin Ma; Wen Xu; Ruotong Si; Xiaoping Xia; Aohan Tang; Lin Zhang; Goulding Keith; et al. (Atmospheric Environment, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Piezocatalysis of graphitic carbon nitride to activate H2O2 for degradation of tetracycline: Influence of piezocatalyst morphology, degradation pathway and toxicity assessment of intermediate products - Lin Miao; Meixuan Wu; Zhuofan Li; Huajun Xu; Baocheng Zhou; Pengfei Sun; Xiaoping Dong (Journal of Water Process Engineering, 2025)

Quantifying Individual Health Status from Multi-omics Data by Health State Manifold - Xinyan Zhang; Chengming Zhang; Yanpu Wu; Xu Lin; Xiaoping Liu; Luonan Chen (Phenomics, 2025)
Quantifying individual health status from increasingly accumulated omics data is essential for both early prevention and intervention of diseases, which attracts great attention from communities of biology and medicine. Most of the existing approaches mainly classify individuals into different catalogues or classes based on phenotypes and biomarkers. However, an individual's health status from a dynamical systems viewpoint can be viewed as a non-equilibrium steady state, which can generally be characterized by two key features, i.e. (1) homeostatic potential that represents the ability of homeostatic resilience to withstand perturbations or maintain functions at the current state/phenotype of this individual and (2) phenotypic potential that represents the state/phenotype of the individual on the whole process from health to disease. Here, we proposed a health state manifold (HSM) method derived from dynamic network biomarker method and diffusion map theory to quantify individual health status with the characterization of such two features in a robust and accurate manner based on multi-omics data. To verify our method, HSM method was applied to the quantification of diabetes mellitus (rat subjects) and the Roux-en-Y Gastric Bypass (human subjects) for both disease progression process and recovery process, which demonstrated its effectiveness and potential for personalized medicine and preventive medicine.

Urea-engineered magnetic ZnFe2O4/Bi2S3 heterojunction for SPC-activated photocatalytic Fenton-like degradation of sulfadiazine - Junge Xu; Haoying Guo; Dong Wang; Yanfang Li; Yuan Lin; Weihao Yu; Yingmu Wang; Rusen Zou; Xiaoping Gao; Baoling Yuan (Chemical Engineering Journal, 2025)

Activation rate-dependent reconstruction of Co-MOFs for efficient CoOOH conversion in oxygen evolution reaction - Youlei Feng; Jinzhi Jia; Zehua Zou; Youxiu Lin; Xuan Zheng; Wenqiang Lai; Xiaoping Chen; Qingxiang Wang; Cailing Xu (Chemical Engineering Journal, 2025)

Ecological connectivity between mangroves and seagrasses increases sediment blue carbon storage - Xinao Guo; Shanshan Song; Lieyi Chen; Conghe Zhang; Shengbin Ye; Yali Ding; Ruikun Gou; Xiaoping Huang; Shuguo Lv; Neil Saintilan; Daniel A. Friess; Guanghui Lin (Estuarine, Coastal and Shelf Science, 2025)

Preparation of high-entropy hydrogen permeation barrier with continuous crystal phase transition via confined magnetic field - Yangbin Liu; Shaohua Zhang; Shuai Wu; Hongshuai Cao; Lin Chen; Xu Zhang; Jiakun Wu; Xiao OuYang; Bin Liao; Xiaoping OuYang (Chemical Engineering Journal, 2025)

In-situ supramolecular self-assembly strategy to fabricate carbon-doped g-C3N4 microtubes: Efficient photocatalytic removal of antibiotics and bacterial inactivation - Hua Lei; Changhao Bian; Fengyu Guo; Xingning Xiao; Ruibin Hu; Jianhan Lin; Wen Wang; Hua Yang; Xiaoping Dong (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Enhanced functional pectin films incorporated with olive fruit extracts prepared by deep eutectic solvents” [Food Packaging and Shelf Life 46 (2024) 101361] - Hua Chen; Kaijie Shang; Xiaonan Bian; Zhiheng Zhao; Yijun Liu; Xue Lin; Lu Wang; Weimin Zhang; Xiaoping Hu; Xuewu Guo (Food Packaging and Shelf Life, 2025)

Human Umbilical Cord Mesenchymal Stem Cells for the Treatment of Systemic Lupus Erythematosus via Glucose Metabolism of CD4+T Cells - Meng Ding; Lu Jin; Shaoxin Cui; Lin Yang; Jingjing He; Xiaoping Wang; Fei Chang; Qun Wang; Xue Liu; Hongtao Jin; Shuran Song; Min Shi; et al. (Stem Cell Reviews and Reports, 2025)

Microbial traits affect soil organic carbon stability in degraded Moso bamboo forests - Xiaoping Tang; Shaofeng Lv; Tongying Wang; Xin Chen; Taoran Sun; Yiyun Xia; Ning Yuan; Yufeng Zhou; Guomo Zhou; Yongjun Shi; Lin Xu (Plant and Soil, 2025)

Engineering phosphorus vacancies in reduced graphene oxide anchored Co2P nanoparticles toward optimal supercapacitive properties - Jiali Zhong; Zhenyuan Ji; Xiang Gao; Zixin Lin; Xiaoyuan Lu; Guoxing Zhu; Keqiang Xu; Peng Song; Xiaoping Shen (Fuel, 2025)

Late Mesozoic Wangxiang Composite Granitic Pluton, South China Block: Implications to Magma Emplacement and Evolution from Geochemical Proxies - Quan Ou; Jing-Yi Liu; Feng Zi; Bruna B. Carvalho; Xiaoping Long; Jian-Qing Lai; Kun Wang; Zi-Qi Jiang; Yi-Zhi Liu; Zheng-Lin Li; Hong-Yun Wang (Journal of Earth Science, 2025)

Chemical compositions, health benefits, safety assessment, and industrial applications of wampee (Clausena lansium (Lour.) Skeels): A comprehensive review - Linhuan Ding; Xiaoze Liu; Tao Fei; Xue Lin; Xiaoping Hu; Lu Wang; Jiachao Zhang (Trends in Food Science & Technology, 2025)

Mechanism and application of environmental engineering and civil engineering: From biological nanoarchitectonics to system engineering - Peidong Su; Meiguangzi Guo; Qing Wen; Xiaoping Zhong; Zaining Li; Tingting Cui; Chunhui Zhang; Junke Zhang; Wentao Jiao; Lin Li (Journal of Environmental Chemical Engineering, 2025)

Synthesis of Zeolite A–X from Coal Fly Ash via Ultrasonic-Alkali Fusion Hydrothermal Method for the Efficient Removal of Cr (VI) From Wastewater - Xiaohui Xu; Kaige Chen; Yong Dai; Xiaoping Xing; Lin Sun (Water, Air, & Soil Pollution, 2025)

Correction to: Distinct expression of three estrogen receptors in response to bisphenol A and nonylphenol in male Nile tilapias (Oreochromis niloticus) - Weiren Huang; Yong Zhang; Xiaoping Jia; Xilan Ma; Shuisheng Li; Yun Liu; Pei Zhu; Danqi Lu; Huihong Zhao; Wenna Luo; Shibai Yi; Xiaochun Liu; et al. (Fish Physiology and Biochemistry, 2025)

Machine learning-assisted SERS sensor for fast and ultrasensitive analysis of multiplex hazardous dyes in natural products - Chengqi Lin; Cheng Zheng; Bo Fan; Chenchen Wang; Xiaoping Zhao; Yi Wang (Journal of Hazardous Materials, 2025)

Harnessing metal-metal interactions for simultaneously boosting photocatalytic hydrogen and benzaldehyde production - Yajie Feng; Chi Lin; Yifei Huang; Bing Li; Yingxin He; Jiangping Ma; Chaogang Ban; Lujie Ruan; Hongxing Jia; Xiaoping Tao; Liyong Gan; Xiaoyuan Zhou (Chemical Engineering Journal, 2025)

Breaking separation bottleneck in sucralose production: Clarifying the obscure mechanism and pre-embedding second solvents for highly selective separation of chlorinated product - Xiaoping Chen; Jiayan Lei; Zhoulin Lv; Zi'ang Chen; Shitong Lin; Zhenming Guo; Huadong Luo; Yingshu Wang; Jingjing Chen; Haohong Li; Huidong Zheng (Chemical Engineering Journal, 2025)

Xenobiotic metabolism activity of gut microbiota from six marine species: Combined taxonomic, metagenomic, and in vitro transformation analysis - Siqi Zhang; Rui Hou; Yuchen Wang; Qianyi Huang; Lang Lin; Hengxiang Li; Shan Liu; Zhijian Jiang; Xiaoping Huang; Xiangrong Xu (Journal of Hazardous Materials, 2024)

Designing a reengineered probiotic yeast to spontaneously degrade residual antibiotics in gut during antimicrobial therapy - Qian He; Zhuoyu Lin; Xiaojing Zhang; Meilin Qin; Yu Huang; Xiaoping Liao; Yahong Liu; Hao Ren; Jian Sun (Journal of Cleaner Production, 2024)

Enhanced functional pectin films incorporated with olive fruit extracts prepared by deep eutectic solvents - Hua Chen; Kaijie Shang; Xiaonan Bian; Zhiheng Zhao; Yijun Liu; Xue Lin; Lu Wang; Weimin Zhang; Xiaoping Hu; Xuewu Guo (Food Packaging and Shelf Life, 2024)

Asymmetric supercapacitors assembled by hollow N, s co-doped carbon spheres decorated FeOOH and Co3S4 nanoparticles - Zhenyuan Ji; Guanxiang Tang; Jingchuang Zhang; Xinghang Chuan; Jiali Zhong; Zixin Lin; Peng Song; Keqiang Xu; Xiaoping Shen (Chemical Engineering Journal, 2024)

CLDN11 deficiency upregulates FOXM1 to facilitate breast tumor progression through hedgehog signaling pathway - Leyi Yang; Xiaoping Wang; Qinghai Lin; Guoyi Shen; Hong Chen (Journal of Molecular Histology, 2024)

Copper Promotes LPS-Induced Inflammation via the NF-кB Pathway in Bovine Macrophages - Hongrui Guo; Lin Jing; Chenglong Xia; Yanqiu Zhu; Yue Xie; Xiaoping Ma; Jing Fang; Zhisheng Wang; Zhicai Zuo (Biological Trace Element Research, 2024)

Effect of antibiotic perturbation on nitrous oxide emissions: An in-depth analysis - Wenjun Yu; Kashif Hayat; Junwei Ma; Xiaoping Fan; Yuyi Yang; Zulin Zhang; Qiaogang Yu; Mingrong Qian; Hui Lin (Critical Reviews in Environmental Science and Technology, 2024)

Noni (Morinda citrifolia) fruit and by-products: A comprehensive review of its chemical compositions, health-promoting effects, safety assessment and industrial applications - Xiaoze Liu; Xue Lin; Xiaoping Hu; Congfa Li; Lu Wang; Tao Fei (Trends in Food Science & Technology, 2024)

Degradation-driven vegetation-soil-microbe interactions alter microbial carbon use efficiency in Moso bamboo forests - Ning Yuan; Fang Fang; Xiaoping Tang; Shaofeng Lv; Tongying Wang; Xin Chen; Taoran Sun; Yiyun Xia; Yufeng Zhou; Guomo Zhou; Yongjun Shi; Lin Xu (Science of The Total Environment, 2024)

Smart nanoscale lamellated supramolecular assemblies overcome biofilm barriers and enhance foliar affinity for efficient control of bacterial diseases - Lizhu Xiang; Xiaohui Wang; Jinghan Yang; Rui Wang; Lin Chen; Xiaoping Bao; Xianfu Mu; Peiyi Wang (Chemical Engineering Journal, 2024)

A target-triggered domino platform for multimode-guided lateral flow immunoassay of multiple β-agonists - Biao Zhang; Yihan Lang; Xuecheng Zhang; Chenxu Zhang; Yulou Qiu; Kai Sun; Xuping Shentu; Xiaoping Yu; Xiaodong Lin (Chemical Engineering Journal, 2024)

Adsorption of metals on aged microplastics in intensive mariculture areas: Aggravating the potential ecological risks to marine organisms - Huihong Du; Pengyu Chen; Xiaoping Lin; Jingyi Zheng; Huatai Liu; Xinhong Wang (Science of The Total Environment, 2024)

Design, synthesis, X-ray crystal structure, and antimicrobial evaluation of novel quinazolinone derivatives containing the 1,2,4-triazole Schiff base moiety and an isopropanol linker - Lan Yang; Muhan Ding; Jun Shi; Na Luo; Yuli Wang; Dongyun Lin; Xiaoping Bao (Molecular Diversity, 2024)

Production of cleavage-resistant phytase transgenic pigs by handmade cloning - Mingyuan Zhang; Jun Zhang; Haowen Yang; Shijin Chen; Xiaoliang Chen; Yuemeng Huang; Baojian Chen; Yanjun Wu; Qinyang Jiang; Yafen Guo; Yingming Wei; Xiukun Lin; et al. (Theriogenology, 2024)

A shallow (<100 km) ilmenite-bearing pyroxenitic source for young lunar volcanism - Chengyuan Wang; Yi-Gang Xu; Le Zhang; Zhiming Chen; Xiaoping Xia; Mang Lin; Feng Guo (Earth and Planetary Science Letters, 2024)

Hydrodynamics and dissolved organic matter components shaped the fate of dissolved heavy metals in an intensely anthropogenically disturbed estuary - Ling Zhang; Yunchao Wu; Jinlong Li; Zhixin Ni; Yuzheng Ren; Jizhen Lin; Xiaoping Huang (Science of The Total Environment, 2024)

Tumor microenvironment responsive multifunctional smart living materials based on engineered bacteria for inducing macrophage polarization to enhance tumor immunotherapy - Ning Jiang; Kui Zhao; Chengcheng Liu; Xiaojuan Zhu; Xumeng Huang; Lin Yang; Xiaoping Yi; Yingping Zhuang; Bangce Ye; Jiangchao Qian; Jiaofang Huang (Chemical Engineering Journal, 2024)

Photothermal-driven Reforming of Methanol Solution into Hydrogen over Ultra-stable Cr-MOF-embedded CuInS2 Heterostructure - Wenting Lin; Jianxian Li; Ziyu Zengcai; Baofang Zhang; Xiaoping Wu; Yunhong Pi; Tiejun Wang (Fuel, 2024)

A sea urchin-shaped nanozyme mediated dual-mode immunoassay nanoplatform for sensitive point-of-care testing histamine in food samples - Biao Zhang; Jingyi Zhang; Yihan Lang; Zicheng Wang; Danfeng Cai; Xiaoping Yu; Xiaodong Lin (Food Chemistry, 2024)

Enocyanin alleviates experimental colitis and restores gut microbiota homeostasis as functional foods - Cang Li; Yu Huang; Meilin Qin; Qian He; Zhuoyu Lin; Xiaojing Zhang; Hao Ren; Dan Xu; Xiaoping Liao; Yahong Liu; Jian Sun (Food Bioscience, 2024)

Flavor characteristics of Shanlan rice wines fermented for different time based on HS-SPME-GC-MS-O, HS-GC-IMS, and electronic sensory analyses - Yaofei Hao; Jianxun Li; Zhiheng Zhao; Wen Xu; Lu Wang; Xue Lin; Xiaoping Hu; Congfa Li (Food Chemistry, 2024)

Cellulose nanocrystals-based fluorescent biocarrier binding GAPDH protein with high affinity in cancer-target doxorubicin delivery - Xiaoping Zhao; Qin Wang; Ning Wang; Ge Zhu; Jingzhi Ma; Ning Lin (Carbohydrate Polymers, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Remediation of Cr(VI)-contaminated soil by ball milling modified zero-valent iron biochar composites: Insights into long-term stability and microbial community - Pengfei Guo; Jinlan Zhang; Yi Zhou; Chenliu Tang; Xiaohui Wang; Xiaoping Gao; Guilan Duan; Aijun Lin; Tingting Zhang; Shangyi Li (Journal of Environmental Chemical Engineering, 2023)

Integrating ferroptosis-related genes (FRGs) and prognostic models to enhance UCEC outcome prediction and therapeutic insights - Weiwei Jin; Xiaoping Zhuang; Yihe Lin; Xiaoying Zhao (Journal of Applied Genetics, 2023)

Effects of Sn-2-palmitate-enriched formula feeding on infants’ growth, stool characteristics, stool fatty acid soap contents and bone mineral content: A systematic review and meta-analysis of randomized controlled trials - Zheqing Zhang; Yingyao Wang; Yan Li; Xiaoping Lin; Zhen Hong; Jiapeng Huang; Xuanrui Zhang; Yuexin Yang; Yixiang Su (Critical Reviews in Food Science and Nutrition, 2023)

The Dof transcription factor COG1 acts as a key regulator of plant biomass by promoting photosynthesis and starch accumulation - Zhuoyun Wei; Haoyong Zhang; Meng Fang; Shuyuan Lin; Mingsong Zhu; Yuxiu Li; Limin Jiang; Tianliang Cui; Yanwei Cui; Hong Kui; Liang Peng; Xiaoping Gou; et al. (Molecular Plant, 2023)

Phenolic profile and α-glucosidase inhibitory potential of wampee (Clausena lansium (Lour.) Skeels) peel and pulp: In vitro digestion/in silico evaluations - Hua Chen; Yousheng Shi; Lu Wang; Xiaoping Hu; Xue Lin (Food Research International, 2023)

Probabilistic framework to evaluate scenario-based building vulnerability under landslide run-out impacts - Xiaoping Sun; Peng Zeng; Tianbin Li; Rafael Jimenez; Qiang Xu; Lin Zhang (Engineering Geology, 2023)

Seawater warming intensifies nickel toxicity to a marine copepod: a multigenerational perspective - Yunlei Zhang; Dongmei Xie; Qingxian Lin; Xiaoping Zhou (Aquatic Toxicology, 2023)

Effects of herbivore on seagrass, epiphyte and sediment carbon sequestration in tropical seagrass bed - Zhijian Jiang; Jialu He; Yang Fang; jizhen Lin; Songlin Liu; Yunchao Wu; Xiaoping Huang (Marine Environmental Research, 2023)

Characterizing annual dynamics of urban form at the horizontal and vertical dimensions using long-term Landsat time series data - Yixuan Wang; Xuecao Li; Peiyi Yin; Guojiang Yu; Wenting Cao; Jinxiu Liu; Lin Pei; Tengyun Hu; Yuyu Zhou; Xiaoping Liu; Jianxi Huang; Peng Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Heterogeneous aggregation between microplastics and microalgae: May provide new insights for microplastics removal - Yuanyuan Su; Liu Gao; Licheng Peng; Xiaoping Diao; Shengyou Lin; Ruiqi Bao; Tariq Mehmood (Aquatic Toxicology, 2023)

High-resolution forest age mapping based on forest height maps derived from GEDI and ICESat-2 space-borne lidar data - Xudong Lin; Rong Shang; Jing M. Chen; Guoshuai Zhao; Xiaoping Zhang; Yiping Huang; Guirui Yu; Nianpeng He; Li Xu; Wenzhe Jiao (Agricultural and Forest Meteorology, 2023)

Foliar uptake of persistent organic pollutants at alpine treeline - Ping Gong; Xiaoping Wang; Yonggang Xue; Lin Zhang; Yongjie Wang (Journal of Hazardous Materials, 2023)

Numerical examination of the geomorphic indicators for lateral fold growth - Lin Gao; Chuanqi He; Gang Rao; Ci-Jian Yang; Xiaoping Yuan; Jingtao Lai; Pengcheng Tang; Lei Wu (Geomorphology, 2023)

Degradation reduces greenhouse gas emissions while weakening ecosystem carbon sequestration of Moso bamboo forests - Ning Yuan; Enhui Wang; Shaofeng Lv; Xiaoping Tang; Tongying Wang; Gang Wang; Yufeng Zhou; Guomo Zhou; Yongjun Shi; Lin Xu (Science of The Total Environment, 2023)

Polystyrene-based hybrid solid acids with tunable hydrophobicity for the synthesis of polyoxymethylene dimethyl ethers from formaldehyde and methanol - Xiaoping Wang; Lin Xu; Jianhua Song; Muhammad Asif Nawaz; Dianhua Liu (Fuel, 2023)

Constructing a region-specific rheological parameter database for probabilistic run-out analyses of loess flowslides - Peng Zeng; Lin Zhang; Tianbin Li; Xiaoping Sun; Liangfu Zhao; Xiujun Dong; Qiang Xu (Landslides, 2023)

Efficient visible-light-driven S-scheme AgVO3/Ag2S heterojunction photocatalyst for boosting degradation of organic pollutants - Yangbin Liu; Nian Liu; Minghua Lin; Caifeng Huang; Zhijun Lei; Hongshuai Cao; Fugang Qi; Xiaoping Ouyang; Yun Zhou (Environmental Pollution, 2023)

Saltwater intrusion regulates the distribution and partitioning of heavy metals in water in a dynamic estuary, South China - Ling Zhang; Yunchao Wu; Zhixin Ni; Jinlong Li; Yuzheng Ren; Jizhen Lin; Xiaoping Huang (Marine Environmental Research, 2023)

Tailored acidic deep eutectic solvents: A multifunctional co-catalyst mediating homogeneous catalysis and heterogeneous separation of ethylene methoxycarbonylation - Jianhua Song; Lin Xu; Xiaoping Wang; Chonghao Chen; Weichong Wang; Haoyu Long; Muhammad Asif Nawaz; Dianhua Liu (Fuel, 2023)

Epoxy-functionalized polyethyleneimine modified epichlorohydrin-cross-linked cellulose aerogel as adsorbents for carbon dioxide capture - Xinjie Chen; Jian Lin; Hanwei Wang; Yushan Yang; Chao Wang; Qingfeng Sun; Xiaoping Shen; Yingying Li (Carbohydrate Polymers, 2023)

Occurrenceand characteristics of microplastics in benthic species from mangrove wetlands of Hainan, South China - Qinzhou Zhang; Jia Xie; Siyuan Ma; Yingya Chen; Fang Lin; Xiaoping Diao (Frontiers in Marine Science, 2023)
Microplastics (MPs) are emerging contaminants that pose a global threat to the environment. Mangrove ecosystems, which contribute to biogeochemical cycles, are vulnerable to various anthropogenic disturbances and chemical pollutants. In this study, the abundance and the characteristics of MPs were investigated in 10 species of benthic organisms, including crabs, bivalves, and snails, from seven typical mangrove distribution areas, with a total of 15 sampling sites in Hainan, South China. The abundance of MPs in each sampling site ranged between 0.83 ± 1.32 and 12.00 ± 0.00 items/individual, with an average of 3.90 ± 3.31 items/individual, while the abundance of MPs varied between 0.17 and 2.00 items/individual for the different species. Fibers (80.13%) were the most abundant MPs, most of the MPs were brown (37.18%) or blue (26.64%), and more than 80% were small-sized plastic (<2 mm). Raman analysis showed that polypropylene (94.44%) was the most dominant type of polymer. In addition, crabs (with an average abundance of 1.10 ± 0.59 items/individual) showed a higher potential for accumulating MPs than the other species investigated in the present study. This study shows that MPs are widely distributed throughout benthic species in the mangrove wetlands of Hainan.

Lamellar-structured anodes based on lithiophilic gradient enable dendrite-free lithium metal batteries with high capacity loading and fast-charging capability - Yucheng Liu; Chuang Sun; Yuhao Lu; Xiaoping Lin; Maohua Chen; Yuansen Xie; Chao Lai; Wen Yan (Chemical Engineering Journal, 2023)

A Bayesian approach to develop simple run-out distance models: loess landslides in Heifangtai Terrace, Gansu Province, China - Xiaoping Sun; Peng Zeng; Tianbin Li; Lin Zhang; Rafael Jimenez; Xiujun Dong; Qiang Xu (Landslides, 2023)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Effects of Zinc Glycinate on Growth Performance, Serum Biochemical Indexes, and Intestinal Morphology of Yellow Feather Broilers - Xiaoping Zhu; Xiuguo Shang; Guozhao Lin; Haojie Li; Xin Feng; Huihua Zhang (Biological Trace Element Research, 2022)
The purpose of this study was to investigate the effects of zinc glycinate (Gly-Zn) on growth performance, serum biochemical index, intestinal morphology, and hepatic metallothionein (MT) mRNA expression in the liver of yellow feather broilers. A total of 540 18-day-old yellow feather broilers were randomly divided into three groups: control group (basal diet), ZnSO 4 group (basal diet plus 60 mg Zn/kg from ZnSO 4 ), and Gly-Zn group (basal diet plus 60 mg Zn/kg from zinc glycinate). Each treatment group had 6 replicates with 30 birds in each replicate. The experiment lasted for 42 days (18 to 59 days of age). The results showed that Gly-Zn supplementation significantly improved the average daily gain (ADG) and average daily feed intake (ADFI) of broilers during 18 to 39 days of age compared with that in the control group ( P < 0.05) but not different from the ZnSO 4 group. The Gly-Zn group had higher glutathione peroxidase (GSH-Px) ( P < 0.05) and lower malondialdehyde (MDA) concentrations than the broilers in the control and ZnSO4 group. It was also observed that zinc content in the tibia of Gly-Zn group broilers was higher than the control and ZnSO4 group ( P < 0.05). The results of intestinal morphology parameters showed that the Gly-Zn group significantly increased the villus height in duodenum and jejunum ( P < 0.05) and decreased crypt depth in duodenum and ileum compared to the control group. However, there were no significant differences between the Gly-Zn group and ZnSO 4 group in duodenum and ileum regarding intestinal morphology parameters. The Gly-Zn group significantly increased mRNA expression of MT in the liver than both control and ZnSO 4 groups ( P < 0.05). Collectively, the results indicated that supplementing 60 mg Zn/kg through zinc glycinate improved growth performance and serum indexes as well as intestinal morphology of yellow feather broilers. It also regulates MT gene expression more effectively than the ZnSO 4 group at the transcriptional level.

Community Structure of Benthic Macrofauna and the Ecological Quality of Mangrove Wetlands in Hainan, China - Ping Li; Jingli Liu; Jiankun Bai; Yifan Tong; Yuchen Meng; Xiaoping Diao; Ke Pan; Xiaoshan Zhu; Guanghui Lin (Frontiers in Marine Science, 2022)
Few studies have systematically assessed the ecological status of mangrove wetlands following the stress of anthropogenic activities in China. This study investigated the spatial and seasonal distribution of benthic macroinvertebrate communities and assessed the ecological quality of mangrove habitats on an island scale in Hainan, China (containing the third largest mangrove area of China and the highest mangrove species richness). For the benthic macrofauna community structure, a total of 102 macrobenthic taxa belonging to 50 families were identified, with Crustaceans, Molluscs, Polychaetes, and Oligochaeta having relative abundances of 52.3%, 36.1%, 10.8%, and 0.8%, respectively. Decapoda and Gastropoda dominated the benthic community abundance. Non-metric multidimensional scaling and an analysis of similarities revealed significantly different macroinvertebrate assemblages among the regions during the two seasons. The South mangroves had the lowest macrofauna species numbers, biodiversity, richness, and abundance. The macrofaunal species richness, Shannon index, Margalef index, abundance, and biomass markedly affected by region and season. As indicated by the biotic indices AMBI (AZTI’s Marine Biotic Index) and M-AMBI, more than half of the mangrove habitats on Hainan Island were slightly to heavily disturbed and had poor to moderate ecological quality. Our results recommend long-term monitoring for evaluating the quality status of mangrove wetlands and avoiding extensive land-use conversion of mangroves. Holistic approaches considering ecological characteristics and combining information on both floral and faunal functionality would contribute to the effective management and conservation of mangroves in disturbed areas.

Poor evidence for host-dependent regular RNA editing in the transcriptome of SARS-CoV-2 - Jinbao Zong; Yanping Zhang; Fenfen Guo; Changyuan Wang; Hong Li; Gaoyang Lin; Wenqing Jiang; Xiaoping Song; Xiufang Zhang; Feng Huang; Min Qi; Xin Zheng (Journal of Applied Genetics, 2022)

EV-T synergizes with AZD5582 to overcome TRAIL resistance through concomitant suppression of cFLIP, MCL-1, and IAPs in hepatocarcinoma - Kui Su; Qian Yuan; Huan Hou; Changhong Ke; Chaohong Huang; Shuyi Li; Jianwu Sun; Xin Yuan; Yue Lin; Yiqing Chen; Huijuan Xin; Xiaoping Liang; et al. (Journal of Molecular Medicine, 2022)

A Machine Learning Methodology for Predicting Geothermal Heat Flow in the Bohai Bay Basin, China - Jifu He; Kewen Li; Xinwei Wang; Nanan Gao; Xiaoping Mao; Lin Jia (Natural Resources Research, 2022)

Characteristics of typical air pollutants in a valley-basin city in South China - Chu Wu; Jibing Li; Xiaoping Lin; Yangzhi Mo; Hui Zhang; Zhihui Liao; Yu Wang; Duohong Chen (Meteorology and Atmospheric Physics, 2022)

Distribution, Temporal Change, and Conservation Status of Tropical Seagrass Beds in Southeast Asia: 2000–2020 - Kenji Sudo; T. E. Angela L. Quiros; Anchana Prathep; Cao Van Luong; Hsing-Juh Lin; Japar Sidik Bujang; Jillian Lean Sim Ooi; Miguel D. Fortes; Muta Harah Zakaria; Siti Maryam Yaakub; Yi Mei Tan; Xiaoping Huang; et al. (Frontiers in Marine Science, 2021)
Although Southeast Asia is a hotspot of global seagrass diversity, there are considerable information gaps in the distribution of seagrass beds. Broad-scale seagrass distribution has not been updated in the global seagrass database by UNEP-WCMC since 2000, although studies on seagrasses have been undertaken intensively in each region. Here we analyze the recent distribution of tropical seagrass beds, their temporal changes, causes of decline and conservation status in Southeast Asia (plus southern mainland China, Taiwan and Ryukyu Island of Japan) using data collected after 2000. Based on the 195 literature published since 2000, we identified 1,259 point data and 1,461 polygon data showing the distribution of seagrass beds. A large discrepancy was found in the seagrass bed distribution between our updated data and the UNEP-WCMC database, mostly due to inaccurate and low resolution location information in the latter. Temporal changes in seagrass bed area analyzed for 68 sites in nine countries/regions demonstrated that more than 60% of seagrass beds declined at an average rate of 10.9% year –1 , whereas 20% of beds increased at an average rate of 8.1% year –1 , leading to an overall average decline of 4.7% year –1 . Various types of human-induced threats were reported as causes for the decline, including coastal development, fisheries/aquaculture, and natural factors such as typhoons and tsunamis. The percentage of seagrass beds covered with existing marine protected areas (MPAs) varied greatly among countries/regions, from less than 1% in Brunei Darussalam and Singapore to 100% in southern Japan. However, the degree of conservation regulation was not sufficient even in regions with higher MPA coverage. The percentage of seagrass beds within EBSAs (Ecologically and Biologically Significant Area determined by the Convention of Biological Diversity) was higher than that within MPAs because EBSAs cover a greater area than MPAs. Therefore, designating EBSAs as legally effective MPAs can greatly improve the conservation status of seagrass beds in Southeast Asia.

A H2O-in-zircon perspective on the heterogeneous water content of crust-derived magmas in southern Tibet - Juntong Meng; Xiaoping Xia; Lin Ma; Ziqi Jiang; Jian Xu; Zexian Cui; Qing Yang; Wanfeng Zhang; Le Zhang (Science China Earth Sciences, 2021)

3D-var assimilation of GTS observation with the gravity wave drag scheme improves summer high resolution climate simulation over the Tibetan Plateau - Qian Xie; Yi Yang; Xiaobin Qiu; Yuanyuan Ma; Anwei Lai; Erliang Lin; Xiaoping Mai (Climate Dynamics, 2021)

Genome-Wide Identification and Comprehensive Analyses of TCP Gene Family in Banana (Musa L.) - Jessica Paola Sánchez Moreano; Xiaoping Xu; Cristina Belén Aucapiña Criollo; Xiaohui Chen; Yuling Lin; Nigarish Munir; Zhongxiong Lai (Tropical Plant Biology, 2021)

The impact of energy-intensive industries on air quality in China’s industrial agglomerations - Xiaoping Zhang; Meihan Lin; Zhenbo Wang; Fengjun Jin (Journal of Geographical Sciences, 2021)

Complement Factor H Displays Opposite Expression Patterns Under Two Situations of Methamphetamine Administration: Acute Exposure and Chronic Dependence - Ming Lin; Jiamin Xu; Zhimin Liu; Liang Qin; Xiaodong Wang; Xiaoping Pu (Neuroscience Bulletin, 2020)

Cortical 3-hinges could serve as hubs in cortico-cortical connective network - Tuo Zhang; Xiao Li; Xi Jiang; Fangfei Ge; Shu Zhang; Lin Zhao; Huan Liu; Ying Huang; Xianqiao Wang; Jian Yang; Lei Guo; Xiaoping Hu; et al. (Brain Imaging and Behavior, 2020)
Mapping the relation between cortical convolution and structural/functional brain architectures could provide deep insights into the mechanisms of brain development, evolution and diseases. In our previous studies, we found a unique gyral folding pattern, termed a 3-hinge, which was defined as the conjunction of three gyral crests. The uniqueness of the 3-hinge was evidenced by its thicker cortex and stronger fiber connections than other gyral regions. However, the role that 3-hinges play in cortico-cortical connective architecture remains unclear. To this end, we conducted MRI studies by constructing structural cortico-cortical connective networks based on a fine-granular cortical parcellation, the parcels of which were automatically labeled as 3-hinge, 2-hinge (ordinary gyrus) or sulcus. On human brains, 3-hinges possess significantly higher degrees, strengths and betweennesses than 2-hinges, suggesting that 3-hinges could serve more like hubs in the cortico-cortical connective network. This hypothesis gains supports from human functional network analyses, in which 3-hinges are involved in more global functional networks than ordinary gyri. In addition, 3-hinges could serve as ‘connector’ hubs rather than ‘provincial’ hubs and they account for a dominant proportion of nodes in the high-level ‘backbone’ of the network. These structural results are reproduced on chimpanzee and macaque brains, while the roles of 3-hinges as hubs become more pronounced in higher order primates. Our new findings could provide a new window to the relation between cortical convolution, anatomical connection and brain function.

Rabies Virus Pseudotyped with CVS-N2C Glycoprotein as a Powerful Tool for Retrograde Neuronal Network Tracing - Xutao Zhu; Kunzhang Lin; Qing Liu; Xinpei Yue; Huijie Mi; Xiaoping Huang; Xiaobin He; Ruiqi Wu; Danhao Zheng; Dong Wei; Liangliang Jia; Weilin Wang; et al. (Neuroscience Bulletin, 2020)

Recycled oceanic crust in the form of pyroxenite contributing to the Cenozoic continental basalts in central Asia: new perspectives from olivine chemistry and whole-rock B–Mo isotopes - Yunying Zhang; Chao Yuan; Min Sun; Ming Chen; Lubing Hong; Jie Li; Xiaoping Long; Pengfei Li; Zhengfan Lin (Contributions to Mineralogy and Petrology, 2019)

Response of drip water temperature to climate variability: a case study in Xiaoyan Cave, southwest China - Xiaojiao Guo; Xiaoping Gong; Daoxian Yuan; Guanghui Jiang; Jianhua Cao; Yushi Lin; Kwong Fai Andrew Lo; Changjie Chen (Hydrological Sciences Journal, 2019)

SCN1A and SCN2A polymorphisms are associated with response to valproic acid in Chinese epilepsy patients - Lihong Shi; Miaomiao Zhu; Huilan Li; Zhipeng Wen; Xiaoping Chen; Jia Luo; Cong Lin; Zanling Zhang (European Journal of Clinical Pharmacology, 2019)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

First complete genome sequence of a virulent bacteriophage infecting the opportunistic pathogen Serratia rubidaea - Shaozhen Xing; Taping Ma; Xianglilan Zhang; Yong Huang; Zhiqiang Mi; Qiang Sun; Xiaoping An; Hang Fan; Shuhui Wu; Lin Wei; Yigang Tong (Archives of Virology, 2017)

Composite likelihood approach to the regression analysis of spatial multivariate ordinal data and spatial compositional data with exact zero values - Xiaoping Feng; Jun Zhu; Pei-Sheng Lin; Michelle M. Steen-Adams (Environmental and Ecological Statistics, 2017)

Population genetic diversity and geographical differentiation of MHC class II DAB genes in the vulnerable Chinese egret (Egretta eulophotes) - Wei Lei; Wenzhen Fang; Xiaoping Zhou; Qingxian Lin; Xiaolin Chen (Conservation Genetics, 2016)

Lack of association between rs10491334 in the CAMK4 gene and longevity in a Chinese population - RONG LIN; YUNXIA ZHANG; DONGJING YAN; XIAOPING LIAO; YUNXIN FU; WANGWEI CAI (Journal of Genetics, 2016)

Complete mitochondrial genomes render the Night Heron genus Gorsachius non-monophyletic - Xiaoping Zhou; Chengte Yao; Qingxian Lin; Wenzhen Fang; Xiaolin Chen (Journal of Ornithology, 2016)

Sex difference of autosomal alleles in populations of European and African descent - Lingjun Zuo; Tong Wang; Xiandong Lin; Jijun Wang; Yunlong Tan; Xiaoping Wang; Xueqing Yu; Xingguang Luo (Genes & Genomics, 2015)

The implications of serial correlation and time-lag effects for the impact study of climate change on vegetation dynamics – a case study with Hulunber meadow steppe, Inner Mongolia - Yong Lin; Xiaoping Xin; Hongbin Zhang; Xu Wang (International Journal of Remote Sensing, 2015)

A novel multiplex PCR assay for individual identification in the vulnerable Chinese Egret (Egretta eulophotes) using molted feathers - Yufei Dai; Wenzhen Fang; Qingxian Lin; Xiaoping Zhou; Xiaolin Chen (Conservation Genetics Resources, 2015)

Characterization of a non-classical MHC class II gene in the vulnerable Chinese egret (Egretta eulophotes) - Wei Lei; Wenzhen Fang; Qingxian Lin; Xiaoping Zhou; Xiaolin Chen (Immunogenetics, 2015)

Mechanism of bFGF-binding Peptide Reversing Adriamycin Resistance in Human Gastric Cancer Cells - Xiangpeng Tan; Xilei Chen; Tao Huang; Wu Luo; Dan He; Xiaomian Lin; Li Song; Xiaoping Wu (International Journal of Peptide Research and Therapeutics, 2014)

A maximum entropy method to extract urban land by combining MODIS reflectance, MODIS NDVI, and DMSP-OLS data - Jinyao Lin; Xiaoping Liu; Kai Li; Xia Li (International Journal of Remote Sensing, 2014)

Lentiviral vector-mediate ATG3 overexpression inhibits growth and promotes apoptosis of human SKM-1 cells - Lin Wang; Jin Song; Jing Zhang; Chen Zhu; Yan Ma; Xiaoping Xu (Molecular Biology Reports, 2014)

Involvement of the nuclear factor-κB pathway in the adhesion of neutrophils to renal tubular cells after injury induced by neonatal postasphyxial serum - Tao Xiong; Wenbin Dong; Hui Fu; Qingping Li; Cunliang Deng; Xiaoping Lei; Lin Guo (Molecular and Cellular Biochemistry, 2014)

Formation, regeneration, and transformation of protoplasts of Streptomyces diastatochromogenes 1628 - Zheng Ma; Jinxiu Liu; Xiaozhen Lin; Xuping Shentu; Yalin Bian; Xiaoping Yu (Folia Microbiologica, 2014)

Mapping Quantitative Trait Loci for Omega-3 Fatty Acids in Asian Seabass - Jun Hong Xia; Grace Lin; Xiaoping He; Bu Yunping; Peng Liu; Feng Liu; Fei Sun; Rongjian Tu; Gen Hua Yue (Marine Biotechnology, 2014)

Nitrogen release from incorporated 15N-labelled Chinese milk vetch (Astragalus sinicus L.) residue and its dynamics in a double rice cropping system - Bo Zhu; Lixia Yi; Yuegao Hu; Zhaohai Zeng; Chaowen Lin; Haiming Tang; Guangli Yang; Xiaoping Xiao (Plant and Soil, 2014)

Development and cross-species transferability of 23 microsatellite markers from the vulnerable Chinese Egret (Egretta eulophotes) using 454 sequencing - Yufei Dai; Xiaoping Zhou; Wenzhen Fang; Qingxian Lin; Xiaolin Chen (Conservation Genetics Resources, 2013)

PCR–RFLP technique for species identification of molted feathers in six species of co-occurring Ardeids - Xunhe Huang; Xiaoping Zhou; Qingxian Lin; Wenzhen Fang; Xiaolin Chen (Conservation Genetics Resources, 2013)

Prospective nested case–control study of feature genes related to leukemic evolution of myelodysplastic syndrome - Yan Ma; Bobin Chen; Xiaoping Xu; Guowei Lin (Molecular Biology Reports, 2013)

An efficient molecular sexing of the vulnerable Chinese egret (Egretta eulophotes) from faeces samples - Xunhe Huang; Xiaoping Zhou; Qingxian Lin; Wenzhen Fang; Xiaolin Chen (Conservation Genetics Resources, 2012)

Characterization, and expression profile of a phenylalanine ammonia lyase gene from Jatropha curcas L. - Jihai Gao; Shuwen Zhang; Feng Cai; Xiaojiang Zheng; Na Lin; Xiaobo Qin; Yangchao Ou; Xiaoping Gu; Xihong Zhu; Ying Xu; Fang Chen (Molecular Biology Reports, 2012)

A novel multiplex PCR assay for species identification in the Chinese Egret (Egretta eulophotes) and Little Egret (E. garzetta) - Xunhe Huang; Xiaoping Zhou; Qingxian Lin; Zhenni Peng; Wenzhen Fang; Xiaolin Chen (Conservation Genetics Resources, 2012)

Overexpression of AtNHX5 improves tolerance to both salt and water stress in rice (Oryza sativa L.) - Meiru Li; Xiaojie Lin; Hongqing Li; Xiaoping Pan; Guojiang Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Common genetic variation in the 3′-untranslated region of gonadotropin-releasing hormone receptor regulates gene expression in cella and is associated with thyroid function, insulin secretion as well as insulin sensitivity in polycystic ovary syndrome patients - Qiaoli Li; Guizhong Yang; Ying Wang; Xiaoping Zhang; Qing Sang; Huan Wang; Xinzhi Zhao; Qinghe Xing; Lin He; Lei Wang (Human Genetics, 2011)

Amino acid sequence analysis and identification of mutations under positive selection in hemagglutinin of 2009 influenza A (H1N1) isolates - Xiaofan Ding; Lifang Jiang; Changwen Ke; Zhan Yang; Chunliang Lei; Kaiyuan Cao; Jun Xu; Lin Xu; Xingfen Yang; Yonghui Zhang; Ping Huang; Weijun Huang; et al. (Virus Genes, 2010)

Distinct expression of three estrogen receptors in response to bisphenol A and nonylphenol in male Nile tilapias (Oreochromis niloticus) - Weiren Huang; Yong Zhang; Xiaoping Jia; Xilan Ma; Shuisheng Li; Yun Liu; Pei Zhu; Danqi Lu; Huihong Zhao; Wenna Luo; Shibai Yi; Xiaochun Liu; et al. (Fish Physiology and Biochemistry, 2010)

BAK1 and BKK1 in Arabidopsis thaliana confer reduced susceptibility to turnip crinkle virus - Hui Yang; Xiaoping Gou; Kai He; Dehui Xi; Junbo Du; Honghui Lin; Jia Li (European Journal of Plant Pathology, 2010)

Subtype identification of the novel A H1N1 and other human influenza A viruses using an oligonucleotide microarray - Xiaoping Kang; Yongqiang Li; Honghe Sun; Weili Wu; Hong Liu; Fang Lin; Chenfeng Qing; Guohui Chang; Qingyu Zhu; Weijun Chen; Yinhui Yang (Archives of Virology, 2010)

A high-density integrative linkage map for Gossypium hirsutum - Zhongxu Lin; Yanxin Zhang; Xianlong Zhang; Xiaoping Guo (Euphytica, 2009)

Transgene integration and organization in Cotton (Gossypium hirsutum L.) genome - Jun Zhang; Lin Cai; Jiaqin Cheng; Huizhu Mao; Xiaoping Fan; Zhaohong Meng; Ka Man Chan; Huijun Zhang; Jianfei Qi; Lianghui Ji; Yan Hong (Transgenic Research, 2008)

Genetic Diversity of Asian Cotton (Gossypium arboreum L.) in China Evaluated by Microsatellite Analysis - Diqiu Liu; Xiaoping Guo; Zhongxu Lin; Yichun Nie; Xianlong Zhang (Genetic Resources and Crop Evolution, 2006)